Broadband Dielectric, Terahertz, and Infrared Spectroscopy of BaTiO3–BaZrO3 Solid Solution: From Proper Ferroelectric over Diffuse and Relaxor Ferroelectrics and Dipolar Glass to Normal Dielectric. Issue 10 (3rd September 2021) - Petzelt, Jan; Bovtun, Viktor; Nuzhnyy, Dmitry; Kempa, Martin; Savinov, Maxim; Paściak, Marek; Kamba, Stanislav; Canu, Giovanna; Buscaglia, Vincenzo
Abstract : Herein, the properties of broadband dielectric spectra up to THz–infrared range of the (1 − x )BaTiO3 ‐ x BaZrO3 (BZT‐ x ) solid solution are reviewed and complemented. This includes the proper ferroelectric ( x = 0), diffuse ferroelectrics (0 < x ≤ 0.2), relaxor ferroelectrics (0.4 ≤ x ≤ 0.8), dipolar glasses ( x > 0.8), and the normal dielectric ( x = 1). The spectra are characterized by an overdamped central mode in the microwave range which weakens on cooling. Except for BaTiO3, the soft mode and central mode do not soften appreciably and do not contribute substantially to the low‐frequency permittivity maximum. The most important dielectric contribution is brought by Cole–Cole relaxation assigned to hopping of Ti ions in the BaTiO3 clusters, which obeys the Arrhenius law with a common activation energy for the whole relaxor range of E a ≈ 181±17 meV and broadens on cooling as described by a temperature‐independent distribution of activation energies. It follows that the polar nanoregions within the BaTiO3 clusters remain very small with temperature‐independent size and frozen boundaries, even if the Ti ions inside them are hopping. This differs from the usual lead‐containing relaxors, in which the polar nanoregions grow on cooling and follow the glass‐like freezing. Abstract : The broadband dielectric spectra up to THz–infrared range of the (1 − x )BaTiO3 ‐ x BaZrO3 solid solution are reviewed and complemented. The soft and central modes do not soften appreciably and the most important dielectric contribution is the relaxation assigned to hopping of Ti ions in the BaTiO3 clusters, which obeys the Arrhenius law with a common activation energy for the whole relaxor range.